Associations of mitochondrial polymorphisms with sporadic colorectal adenoma. Issue 5 (1st February 2018) - Thyagarajan, Bharat; Guan, Weihua; Fedirko, Veronika; Barcelo, Helene; Ramasubramaian, Ramya; Gross, Myron; Goodman, Michael; Bostick, Roberd M.
Abstract : Somatic mutations in mitochondrial DNA have been reported in colorectal adenomatous polyps (adenomas), the precursors to most colorectal cancers. However, there are no reports of associations of germline variation in mitochondrial DNA with adenoma risk. We investigated associations of germline polymorphisms in the displacement loop (D‐loop) and non‐D‐loop region of the mitochondrial genome with incident, sporadic colorectal adenoma in three pooled colonoscopy‐based case‐control studies ( n  = 327 adenoma cases, 420 controls) that used identical methods for case and risk factor ascertainment. We sequenced a 1124 bp fragment to identify all genetic variation in the mitochondrial D‐loop region, and used the Sequenom platform to genotype 64 tagSNPs in the non‐D‐loop region. We used multivariable unconditional logistic regression to estimate associations of the polymorphisms with adenoma. The odds ratios (OR) for associations of four polymorphisms in the HV1 region (mt16294, mt16296, mt16278, mt16069) with adenoma were 2.30, 2.63, 3.34, and 0.56, respectively; all 95% confidence intervals (CI) excluded 1.0, however, after correction for multiple comparisons, none of the findings remained statistically significant. Similar results were found for six polymorphisms in the non‐D‐loop region. In the HV1 region poly C tract, relative to those with 5 repeats, the ORs for those with fewer or more repeats were, respectively, 2.29 (95%CI 1.07‐4.89) and 0.63 (95%CI 0.36‐1.08), but repeat numbers in the HV2 region were not associated with adenoma. These findings suggest that mitochondrial D‐loop HV1 region polymorphisms may be associated with colorectal adenoma risk and support further investigation.